Characterisation of C101248: A novel selective THIK-1 channel inhibitor for the modulation of microglial NLRP3-inflammasome. (15th February 2023) - Ossola, Bernardino; Rifat, Ali; Rowland, Anna; Hunter, Helen; Drinkall, Samuel; Bender, Clare; Hamlischer, Mayida; Teall, Martin; Burley, Russell; Barker, Daneil F.; Cadwalladr, David; Dickson, Louise; et al.
Abstract: Neuroinflammation, specifically the NLRP3 inflammasome cascade, is a common underlying pathological feature of many neurodegenerative diseases. Evidence suggests that NLRP3 activation involves changes in intracellular K + . Nuclear Enriched Transcript Sort Sequencing (NETSseq), which allows for deep sequencing of purified cell types from human post-mortem brain tissue, demonstrated a highly specific expression of the tandem pore domain halothane-inhibited K + channel 1 (THIK-1) in microglia compared to other glial and neuronal cell types in the human brain. NETSseq also showed a significant increase of THIK-1 in microglia isolated from cortical regions of brains with Alzheimer's disease (AD) relative to control donors. Herein, we report the discovery and pharmacological characterisation of C101248, the first selective small-molecule inhibitor of THIK-1. C101248 showed a concentration-dependent inhibition of both mouse and human THIK-1 (IC50: ∼50 nM) and was inactive against K2P family members TREK-1 and TWIK-2, and Kv2.1. Whole-cell patch-clamp recordings of microglia from mouse hippocampal slices showed that C101248 potently blocked both tonic and ATP-evoked THIK-1 K + currents. Notably, C101248 had no effect on other constitutively active resting conductance in slices from THIK-1-depleted mice. In isolated microglia, C101248 prevented NLRP3-dependent release of IL-1β, an effect not seen in THIK-1-depleted microglia. In conclusion, we demonstrated that inhibiting THIK-1 (a microglia specific gene that is upregulated in brains from donors with AD) using a novel selective modulator attenuates the NLRP3-dependent release of IL-1β from microglia, which suggests that this channel may be a potential therapeutic target for the modulation of neuroinflammation in AD. Highlights: THIK-1 mRNA and protein are highly enriched in microglia in human cortical tissue. THIK-1 mRNA is increased in microglial from AD brains compared to non-AD controls. Disclosure of C101248, the first selective small-molecule to block THIK-1 currents. THIK-1 inhibition prevented the NLRP3-dependent release of IL-1β from microglia.